ANTITOXIC ROLE OF TOCOPHEROL IN STABILIZATION OF BLOOD INDICES IN ACUTE HYPOXIA (Proceedings of the YSU B: Chemical and Biological Sciences, 2019)
The character of deviations of blood clotting indices in acute hypoxia was studied, as this testifies to the development of hypercoagulation and thrombotic status. Maximum changes are recorded after the 3-hour period exposure, which indicates the deeper impact of the factor within the timeframe. Tocopherol use is considered effective, which as a powerful antioxidant and antihypoxant helps to stabilize blood cells membranes to create favorable conditions for biological oxidation processes and regulation of coagulation parameters and clotting time.
Keywords: acute hypoxia, blood clotting indices, tocopherol